Genotype-specific RNA probes for direct identification of wild polioviruses by blot hybridization. - De, L (1997)
We have developed RNA probes for the direct identification of wild poliovirus isolates by blot hybridization. The probes are complementary to sequences of the first 30 to 32 codons of VP1, which evolve more extensively (approximately 1.5-fold) than the rest of VP1. To illustrate our general approach, we describe the design of probes specific to each of four major genotypes recently endemic (1981 to 1991) to the Americas: Andean type 1, Brazil type 1, Brazil type 3, and Central America-Mexico type 3. A wild isolate of each genotype was selected according to molecular and epidemiologic criteria to be representative of the principal lineages in circulation. Variable VP1 sequences of the representative isolates were amplified by the reverse transcriptase PCR and were inserted into a plasmid vector containing a T7 promoter. The in vitro transcripts, labeled with digoxigenin, served as probes. These formed stable hybrids only with RNAs of isolates of the corresponding genotypes. Hybrids were detected by a sensitive chemiluminescence assay, capable under normal diagnostic conditions of detecting specific wild poliovirus sequences in samples containing up to a 100-fold excess of Sabin vaccine strain-related sequences of the same serotype.